1992
DOI: 10.1130/spe272-p127
|View full text |Cite
|
Sign up to set email alerts
|

The Layos Granite, Hercynian Complex of Toledo (Spain): an example of parautochthonous restite-rich granite in a granulitic area

Abstract: ABSTRACf: The Layos Granite forms elongated massifs within the Toledo Complex of central Spain. It is late-tectonic with respect to the F2 regional phase and simultaneous with the metamorphic peak of the region, which reached a maximum temperature of 800-850°C and pressures of 400-600 MPa. Field studies indicate that this intrusion belongs to the "regional migmatite terrane granite" type. This granite is typically interJayered with sill-like veins and elongated bodies of cordierite/ garnet-bearing leucogranite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Nevertheless, in several places there are kilometer-sized outcrops of these granites that are considered to be superposed sheets of similar restite-rich granites. A petrographic, mineralogical, geochemical, and petrogenetic discussion of these granites is given by Barbero and Villaseca [ 1992)] They proposed a restiteunmixing model to explain the mineralogy and chemical variability, in which the restitic end-member was represented by the granulitic migmatites of the area, and the liquid end-member by the Cervatos leucogranites.…”
Section: Anatectic Granitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in several places there are kilometer-sized outcrops of these granites that are considered to be superposed sheets of similar restite-rich granites. A petrographic, mineralogical, geochemical, and petrogenetic discussion of these granites is given by Barbero and Villaseca [ 1992)] They proposed a restiteunmixing model to explain the mineralogy and chemical variability, in which the restitic end-member was represented by the granulitic migmatites of the area, and the liquid end-member by the Cervatos leucogranites.…”
Section: Anatectic Granitesmentioning
confidence: 99%
“…A detailed discussion of the petrography, mineral chemistry and petrogenesis of these granitoids is given by Barbero and Villaseca [1992] and Barbero [1992].…”
Section: Layos Resrite-rich Granitesmentioning
confidence: 99%
See 1 more Smart Citation
“…At least one thin section was made for each stele, as well as of the sampled metasedimentary and granitic rocks cropping out in the surrounding area, for comparison. Previous geological studies carried out within the studied area were also used (Andonaegui & Barrera, 1984;IGME, 1985aIGME, , 1985bIGME, , 1985cIGME, , 1987IGME, , 1992IGME, , 2008aIGME, , 2008bIGME, , 2008cIGME, , 2009aIGME, , 2009bIGME, , 2009cITGE, 1989;Merino Martínez, 2014;Villaseca et al, 2014) These geochemical data can be found in Andonaegui and Barrera (1984), Andonaegui (1990), Barbero and Villaseca (1992), Villaseca and Barbero (1994), Barbero (1995), Andonaegui and Villaseca (1998) Figure 4a and Table 3), suggesting that these rocks present an excess of aluminum with respect to calc-alkali elements, which is responsible of the presence of aluminum-rich minerals (i.e., biotite, muscovite, cordierite, tourmaline, andalusite, sillimanite and/or garnet). The main petrographic and geochemical features of each stele, according to its lithological nature, are described below.…”
Section: Petrographic Techniquesmentioning
confidence: 99%
“…The Bandelierkop formation leucosomes exhibit both these characteristics strongly. The compilation of metasedimentary rock mafic residuum and leucosome compositions was sourced from: Bea and Montero (1999), Barbero and Villaseca (1992), Barbey et al (1990), Braun et al (1996, Carrington and Watt (1995), Chavagnac et al (2001), Del Moro et al (2000, Johannes et al (2003), Martignole and Martelat (2003), Mengel et al (2001), Sawyer et al (1999), , Villaseca et al (2001), White et al (2004), and Whitney and Irving (1994) et al (2014), the mechanisms that control the formation of high-temperature K 2 O-poor felsic leucosomes have not yet been tested by thermodynamically constrained modelling. One reason for this is the difficulty of designing phase equilibrium modelling experiments to predict disequilibrium behaviour.…”
mentioning
confidence: 99%